Dynamically Driven Evolution of Molecular Gas in the Barred Spiral Galaxy M83 Traced by CO J = 2–1/1–0 Line Ratio Variations - Jin Koda; Fumi Egusa; Akihiko Hirota; Amanda M Lee; Tsuyoshi Sawada; Fumiya Maeda (The Astrophysical Journal)
We show the variations of the CO J = 2–1/1–0 line ratio ( R _21/10 ) across the barred spiral galaxy M83, using the 46 pc resolution data from the Atacama Large Millimeter/submillimeter Array. The R _21/10 map clearly evidences the systematic large-scale variations as a function of galactic structures. Azimuthally, it starts from low R _21/10 ≲ 0.7 in the interarm regions and becomes high ≳0.7 in the bar and spiral arms, suggesting that the density and/or kinetic temperature of molecular gas increase by about a factor of 2–3. This evolution is seen even in the parts of spiral arms without star formation, and R _21/10 is often elevated even higher to ∼0.8–1.0 when H ii regions exist in the vicinity. Radially, R _21/10 starts very high ≳1.0 at the galactic center, remains low ≲0.7 in the bar region, increases to ≳0.7 around the bar end, and again decreases to ≲0.7 in the rest of disk where the spiral arms dominate. The evolutionary sequence is synchronized with galactic rotation, and therefore, it is determined largely by the galactic structures and dynamics and is governed by the galactic rotation timescales. The R _21/10 map also shows that the influence of stellar feedback is localized and limited. Massive, large, and non-star-forming molecular structures have low R _21/10 , which also suggests that the bulk molecular gas in the disk is not regulated by stellar feedback, but more likely by galactic structures and dynamics. These results are consistent with suggestions by the earlier studies of the Milky Way and other barred spiral galaxies, and thus, are likely general among barred spiral galaxies in the local Universe.